PIPAC - overview of the method and first use in the Czech Republic - Hoskovec, D; Krška, Z; Vočka, M; Dytrych, P (Rozhledy v chirurgii, 2020)
PIPAC is a new technique for intra-abdominal administration of aerosol chemotherapy in a gaseous environment (capnoperitoneum). It can be indicated for peritoneal spread of various origins, most commonly ovarian cancer, stomach cancer and colorectal cancer. Due to its mini-invasiveness, the application can be repeated. The article provides a brief overview of current views of PIPAC and describes the first experience with PIPAC in the Czech Republic.
Keywords: protokoly protinádorové kombinované chemoterapie; Česká republika; Peritoneal Neoplasms; nádory vaječníků; peritoneal carcinomatosis – PIPAC – HIPEC; lidé; aerosoly; Aerosols; Female; Ovarian Neoplasms; Czech Republic; peritoneální nádory; ženské pohlaví; Antineoplastic Combined Chemotherapy Protocols; Humans